Immigration and Labor Market Mobility in Israel, 1990 to 2009 - Cohen Goldner, Sarit (Book collections on Project MUSE., 2012)
A study of the labor market integration of highly skilled Soviet immigrants to Israel that formulates dynamic models of job search and human capital investment.